2014
DOI: 10.1152/jn.00628.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dual tasking on intentional vs. reactive balance control in people with hemiparetic stroke

Abstract: To examine the effect of a cognitive task on intentional vs. reactive balance control in people with hemiparetic stroke (PwHS). Community-dwelling PwHS (n = 10) and healthy, age-similar controls performed two tests, which included the Limits of Stability Test (intentional control) and the Motor Control Test (reactive control), under single-task (ST) and dual-task (DT) conditions (addition of a cognitive task). Cognitive ability was measured on a word list generation task by recording the number of words enumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In contrast to our findings, previous studies examining the cognitive-motor interference of reactive balance have demonstrated that dual tasking affects the performance only on the cognitive task (motor-related cognitive interference) without affecting the reactive balance task (Brauer et al, 2002;Maki et al, 2001;Zettel et al, 2008). As most of these studies have examined the cognitive-motor interference using small magnitude perturbations, it is postulated that the individuals are able to rapidly switch attention to the reactive balance task, and maintain postural stability at the cost of the cognitive task performance when perturbing intensities are small (Brauer et al, 2002;Brown et al, 1999;Maki & McIlroy, 2007;Maki et al, 2001;Subramaniam, Hui-Chan, & Bhatt, 2014;Zettel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, previous studies examining the cognitive-motor interference of reactive balance have demonstrated that dual tasking affects the performance only on the cognitive task (motor-related cognitive interference) without affecting the reactive balance task (Brauer et al, 2002;Maki et al, 2001;Zettel et al, 2008). As most of these studies have examined the cognitive-motor interference using small magnitude perturbations, it is postulated that the individuals are able to rapidly switch attention to the reactive balance task, and maintain postural stability at the cost of the cognitive task performance when perturbing intensities are small (Brauer et al, 2002;Brown et al, 1999;Maki & McIlroy, 2007;Maki et al, 2001;Subramaniam, Hui-Chan, & Bhatt, 2014;Zettel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in the SG took more time to perform the maze task as compared with the CG in most stages of the practice. This finding is interpreted as a consequence of the lesion in brain areas (e.g., the cerebral cortex) [52] that might negatively affect the planning and execution of motor tasks that requires spatial memory and organization [39]. It is well known that the ability to find the right way into a novel or familiar environment (such as in the maze task) is a multifactorial function [53].…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, traditional rehabilitation programs do not generally include DT as a therapeutic strategy during therapeutic training. 8 Studies examining postural control and balance activities following a stroke have reported that DT exercises substantially deteriorate both motor and cognitive components of balance control owing to cognitive-motor interference (CMI), [9][10][11] that is, a decline in the performance of one or both (cognitive and motor task) components, relative to the performance of each task component separately during DT performance. CMI also considerably affects gait parameters following stroke, such as decreased gait speed and increased stride duration.…”
Section: Three-dimensional Trainingmentioning
confidence: 99%
“…Studies examining postural control and balance activities following a stroke have reported that DT exercises substantially deteriorate both motor and cognitive components of balance control owing to cognitive–motor interference (CMI), 9 11 that is, a decline in the performance of one or both (cognitive and motor task) components, relative to the performance of each task component separately during DT performance.…”
Section: Introductionmentioning
confidence: 99%